Non-destructive in-operando investigation of catalyst layer degradation for water electrolyzers using synchrotron radiography. (June 2020) - Panchenko, Olha; Carmo, Marcelo; Rasinski, Marcin; Arlt, Tobias; Manke, Ingo; Müller, Martin; Lehnert, Werner
Abstract: Unveiling degradation mechanisms is a difficult task encountered when characterizing materials and components for water electrolyzers, where for stationary applications these cells are expected to run for 50.000 h or more. From a R&D perspective, this incredibly long time-dependence makes the assessment of degradation mechanisms almost impracticable. Therefore, novel and advanced methodologies need to be demonstrated, aiding scientists to more quickly identify and effectively tackle the different stressors that lead to degradation. Here we show a novel approach where in-operando synchrotron radiography was used to access real-time electrode degradation. A real catalyst-coated membrane was assembled and tested under real water splitting conditions, where iridium catalyst detachment could be observed and semi-empirically quantified. For the first-time, we have also demonstrated a way to visualize and identify where bubble formation inside the catalyst-coated membrane occurs, and how it can trigger electrode degradation. This study shall open new avenues to quickly and properly unveil degradation mechanisms, methods that could also be used for other electrochemical devices such as batteries, fuel cells and solar water splitting technologies. Graphical abstract: Image 1 Highlights: A real-time catalyst layer detachment in a PEM electrolysis cell, visualized by in-operando synchrotron radiography. Most of the hydrogen is evolved at the interface between the catalyst layer and membrane. Mutual catalyst migration took place. No platinum or iridium band was detected inside the membrane.